2022
DOI: 10.7554/elife.76712
|View full text |Cite
|
Sign up to set email alerts
|

Associative learning drives longitudinally graded presynaptic plasticity of neurotransmitter release along axonal compartments

Abstract: Anatomical and physiological compartmentalization of neurons is a mechanism to increase the computational capacity of a circuit, and a major question is what role axonal compartmentalization plays. Axonal compartmentalization may enable localized, presynaptic plasticity to alter neuronal output in a flexible, experience-dependent manner. Here we show that olfactory learning generates compartmentalized, bidirectional plasticity of acetylcholine release that varies across the longitudinal compartments of Drosoph… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 91 publications
1
16
0
1
Order By: Relevance
“…This revelation raises an important question. Since rut is required for learninγ4 3 , 44 , 48 and learning induces MB ACh plasticity, 30 , 31 how does rut contribute to learning-induced plasticity of ACh odor responses given that odor-induced ACh responses are independent of rut ( Figure 5E )? This question led us to explore the role of dDA1 and rut in learning and learning-induced plasticity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This revelation raises an important question. Since rut is required for learninγ4 3 , 44 , 48 and learning induces MB ACh plasticity, 30 , 31 how does rut contribute to learning-induced plasticity of ACh odor responses given that odor-induced ACh responses are independent of rut ( Figure 5E )? This question led us to explore the role of dDA1 and rut in learning and learning-induced plasticity.…”
Section: Resultsmentioning
confidence: 99%
“…We first confirmed that knockdown of rut and dDA1 in the MB eliminates learning ( Figure 5F ). We then focused efforts on imaging ACh plasticity in the γ2 compartment in flies with reduced rut and dDA1 expression since aversive training generates a CS+-specific (conditioned stimulus) depression in γ2 ACh output, 30 and this depression is mirrored in Ca 2+ responses in the downstream MBON-γ2α′1. 34 We found that knockdown of rut, while having no effect on odor-induced release of ACh from MBn prior to training, occludes the CS+-specific depression in γ2 ACh output ( Figures 5G and S6D′ ).…”
Section: Resultsmentioning
confidence: 99%
“…Moderate reductions in Cac biosynthesis do not result in comparable depletion of Cac at AZs, indicating that AZs are buffered against alterations in Cac transcription or translation. Kenyon cells in the Drosophila mushroom body maintain normal presynaptic release following weak Cac RNAi knockdown, but fail to potentiate presynaptic release during odor conditioning, suggesting that Cac buffering also occurs in the CNS and its biosynthesis may become rate-limiting during certain forms of presynaptic plasticity ( Stahl et al, 2022 ). We also find that Cac overexpression fails to increase Cac abundance at AZs, indicating that Cac biosynthesis does not rate-limit AZ Cac accumulation and suggesting that competition between Cac channels for AZ localization.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the relative intensity in MB was high for rACh, surpassing even that of G7f (Fig. 2b, c), implying a potentially superior role of ACh in MB 39,47 . At the voxel level, there was substantial variation in response intensity even within a single brain region (Figs.…”
Section: Mainmentioning
confidence: 89%